Module Development of Inquiry Based On Learning History Class XI Using Model Borg and Gall - Situmorang, Arman; Handayani, Sri; Swastika, Kayan (History Education, University of Jember, 2017)
Learning material used learners in learning have not been able to grow the ability to seek and find their own and construct their understanding. Different speed of understanding and limited time in implementing learning in school resulted in learners unable to learn independently and directed and learn to solve problems systematically. For that the need for the use of innovative teaching materials in the form of module-based inquiry. Through the use of this inquiry-based module, learners are expected to develop their ability to learn through their own initiative and be able to solve problems critical, logical, and analytical learning so that they can formulate their own inventions full confidence. This study identifies the student's needs analysis of the innovative teaching materials that learners want. This type of research is development research. Expert validation in this research is learning design expert, learning material expert and linguist. Research subjects in small group test as 10 children, big group test as 2 class in school faithful. Data collection techniques: observation, questionnaire, interview and documentation. A student needs analysis of inquiry-based module was obtained by questionnaire dispersion in three schools with class selection in low learning category. The needs analysis of learners measured through questionnaires used data with a presentation of needs of 78%. The results of validation of 60% design learning experts, 82% learning material experts and 82% language validation. One to one test result is 91%, small group test in SMAN 5 Jember class XI IIS 2 get t test (2,55) and SMAN Plus Sukowono class XI IIS 1 obtained t test (2,83). Large group test in SMAN 5 Jember class XI IIS 1 obtained data t test (2,83), class XI IIS 2 obtained data t test (3,16). Large group test in SMAN Plus Sukowono class XI IIS 1 was obtained t test (3,16) and class XI IIS 2 t test (2,91). Keywords: Learning Resources, Inquiry-Based Modules